Inferior vena cava injury in the area of ??its diaphragmatic crossing - Gomez Fossati, Carlos; A. Crestanello, Francisco; C. Praderi, Raul (Cirugía del Uruguay, 1971)
A bullet wound of the inferior vena cava, in the area of its passage by the diaphragmiwis successfully treated by the authors. The paper refers to the diagnosis and discusses the path followed by the bullet, analyzing it after revising the anatomy of the region; to the bleeding alternatives of the wound and to the therapy applied.